Janpadodhwansa and Environmental Health: Re-visiting Ancient Perception in the Modern Period - Dr Rohan Verma; Dr. shashi Bala Saini; Dr Rahul Suthar; Dr.Laxman Singh (Revista Electronica de Veterinaria, 2024)
It seems that the Indian system of medicine, i.e. Ayurveda, has more to offer in addressing the epidemics and natural calamities from its concept of 'Janpadodhwansa', which means mass destruction of living beings resulted as a essay by environmental imbalances. This essay describes the traditional concept of Janpadodhwansa, links it to current environmental and public health problems, and suggests community-based integrative solutions. We also stress the enduring importance of caring for and sharing our environment, and how all people have an obligation to each other in this responsibility, which sustains civilisation, reinforced by a retelling that draws from both early scientific tradition as well as drawing upon contemporary science.